PENGEMBANGAN INFRASTRUKTUR DESA BERBASIS BUDAYA KERAJINAN WAYANG KULIT GUNA MENINGKATKAN PEMASARAN DI PUCUNG, DESA WUKIRSARI, KABUPATEN BANTUL, YOGYAKARTA - Elisabet Asalia Sarita Putri; Haniek Listyorini; Sri Yuwanti; Suwarti Suwarti (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2023)
Infrastructure development is the duty and responsibility of both the Central Government, Provincial Government and Regency/City Regional Governments in accordance with the division of government affairs. One of the places in Bantul Regency that introduces leather puppet crafts to the wider community is Pucung as a center for shadow puppets. The development of village infrastructure based on the wayang kulit craft culture needs to identify the efforts of wayang kulit craftsmen in overcoming marketing barriers, infrastructure development efforts that have been carried out so far, and prioritized infrastructure to be equipped with the aim of increasing the marketing of wayang kulit crafts. This study uses qualitative methods with observations and interviews. The results of this study are that craftsmen market wayang kulit crafts online and digitally E-commerce to overcome the obstacles they face, the infrastructure related to the marketing of leather puppets that has been developed so far is a means of communication in the form of internet and WIFI, and infrastructure that is prioritized to be equipped is e-commerce digital marketplace.